1990
DOI: 10.1073/pnas.87.17.6522
|View full text |Cite
|
Sign up to set email alerts
|

Role of 1,25-dihydroxycholecalciferol in growth-plate cartilage: inhibition of terminal differentiation of chondrocytes in vitro and in vivo.

Abstract: The effects of vitamin D metabolites on alkaline phosphatase [ALPase; orthophosphoric-monoester phosphohydrolase (alkaline optimum), EC 3.1.3.1] activity, a marker ofterminal differentiation, in chondrocyte cultures and growth plates in vivo were examined. In cultures of pelleted rabbit growth-plate chondrocytes, 1,25-dihydroxycholecalciferol (1,25-dihydroxyvitamin D3) increased the contents of DNA and macromolecules containing uronic acid (proteoglycans). It also decreased ALPase activity with an ED50 of <1 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The active metabolite of vitamin D3 binds to the nuclear receptor VDR, which is expressed in both osteoblastic cells of bone (50)(51)(52) and in cartilaginous cells of the growth plate (53)(54)(55). Here we have confirmed that the PTHR is also expressed in osteoblastic cells of bone and in chondrocytes located mainly in the proliferative zone and the upper hypertrophic zone of the growth plate.…”
Section: Discussionsupporting
confidence: 72%
“…The active metabolite of vitamin D3 binds to the nuclear receptor VDR, which is expressed in both osteoblastic cells of bone (50)(51)(52) and in cartilaginous cells of the growth plate (53)(54)(55). Here we have confirmed that the PTHR is also expressed in osteoblastic cells of bone and in chondrocytes located mainly in the proliferative zone and the upper hypertrophic zone of the growth plate.…”
Section: Discussionsupporting
confidence: 72%
“…This could be due either to a delay in hypertrophic chondrocyte apoptosis or to acceleration of proliferating chondrocyte differentiation to hypertrophic cells; evidence from in vitro studies implicates the latter mechanism. Treatment of rabbit growth plate chondrocytes with 1,25(OH) 2 -vitamin D 3 results in reduced alkaline phosphatase activity and a delay in differentiation to the hypertrophic phenotype (Kato et al 1990). These effects are opposite to those induced by T 3 .…”
Section: 25(oh) 2 -Vitamin D 3 Effects On Growth and Expression Of mentioning
confidence: 99%
“…Although vitamin D deficiency in vivo results in rickets, with increased width of the hypertrophic zone of the growth plate, the mechanism underlying this phenomenon is not understood. Possible explanations include accelerated conversion of chondrocytes to the hypertrophic state, delayed hypertrophic cell death, or a deficit of osteoclasts or chondroclasts in the rachitic bone, since it is known that osteoclast formation is facilitated by vitamin D [22].…”
Section: Discussionmentioning
confidence: 99%
“…Kato [22] and co-workers 48 R. Tracy Bullock et (11. I Journal of Orthoprredic Research 19 (2001 i 43-49 investigated the possibility that 1,25(OH), vitamin D3 slows the conversion of chondrocytes to the hypertrophic state in three-dimensional pellet cultures of growth plate chondrocytes from the ribs of normal or rachitic rabbits.…”
Section: Discussionmentioning
confidence: 99%